A degradação ambiental nos municípios do Rio Grande do Sul e a relação com os fatores de desenvolvimento rural - Pinto, Nelson Guilherme Machado (2014)
Environmental degradation presents itself as a major challenge for a variety of countries. This fact is due to the increased knowledge obtained regarding the changes that the global environment has suffered. This phenomenon can be understood as the destruction, damage or wearing that is generated in the environment by human activities and inherent to nature. In this sense, many of the changes originated from environmental degradation are consequences of agricultural activities, and in the Brazilian scenario, this issue also arises from livestock exploration, given the importance of this type of activity for the country. Environmental degradation can be measured by the creation of an Agricultural Environmental Degradation Index (IDAA). Due to the impacts of environmental degradation caused by livestock activities, there are changes occurring regarding the rural development of the localities, because the rural environment is in a reality closer to the occurrence of this phenomenon for this type of activity. Within the context of Rio Grande do Sul, there is a lack of studies that measure environmental degradation. In order to characterize the agricultural environmental degradation in Rio Grande do Sul and also fill this gap in the literature regarding the relationship between this phenomenon and other aspects of development of the regions, the research problem of this study can be summarized as follows: what is the pattern of agricultural environmental degradation of the cities from Rio Grande do Sul and how this phenomenon is impacted by factors of rural development in two distinct periods of time. Therefore, this study aimed to analyze the pattern of agricultural environmental degradation of the cities in the state of Rio Grande do Sul and see how this pattern is affected by the factors of rural development in these same cities in two different periods of time. In this sense, the methodology used was the Agricultural Environmental Degradation Index (IDAA) as a proxy for agricultural environmental degradation and the technique of factor analysis was used to find the determinants of rural development of cities in the state. In order to study the impact of these factors on agricultural environmental degradation of Rio Grande do Sul, a regression model with panel data was estimated by the method of Fixed Effects. The values of agricultural environmental degradation for the mesoregions of Rio Grande do Sul shown to be high for the two years studied, and the central-eastern mesoregion presented the greatest degradation averages, with IDAA values of 84.58% in 1996 and 85.16% in 2006.Referring to its scale, this mesoregion also showed the worst results, with 47.62% of its cities with degradation patterns with scales of degree above the average value in 1996 and 2006. Regarding the variation of agricultural environmental degradation in the two years surveyed, there is a small variation in the value of the index from one year to another, ie, only 0.02%.The factors of rural development found in Rio Grande do Sul were Conditions of Housing and Rural Education (F1), Structure and Performance of the Agricultural Sector (F2); Leverage and Correction of Rural Production (F3), Agricultural Production Area (F4); Rural Electricity (F5) and Economic and Financial Rural (F6).In the relationship between IDAA and the factors, all coefficients were statistically significant. F1, F3 and F5 presented a positive relationship with degradation, demonstrating that the more developed the regions are, in relation to these aspects, the greater the levels of degradation, which are justified, respectively, by the environmental dilemma of Rio Grande do Sul, because of the overuse of these practices and the irrational use of electrical resources. In the contrary, F2, F4 and F6 showed a negative relationship, justified, respectively, by agro-ecological assumptions, by concerns regarding environmental issues and the inverse relationship between degradation and the economic aspect.